1992
DOI: 10.1111/j.1365-246x.1992.tb00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic intensity variations in red beds of the Lodève Basin (southern France) and their bearing on the magnetization acquisition process

Abstract: An investigation of small-scale variations of magnetization of a red bed sequence in the Permian Lodbve Basin (southern France) has been carried out by means of 512 disc-shaped samples, each 25 mm in diameter and about 6 mm thick. It is found that magnetic intensity variations reaching an order of magnitude can occur over stratigraphic distances of only a few centimetres. These fluctuations show a clear lithostratigraphic control with intensity peaks systematically located at bed tops. Rock magnetic experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(Re)magnetization associated with periodic water saturation of continental deposits has been recognised by several authors (Burbank & Li 1985;Hus & Geeraerts 1986;Maillol & Evans 1992). Laboratory experiments confirm the validity of this process (Irving & Major 1964;McIntosh 1993).…”
Section: Discussionmentioning
confidence: 76%
“…(Re)magnetization associated with periodic water saturation of continental deposits has been recognised by several authors (Burbank & Li 1985;Hus & Geeraerts 1986;Maillol & Evans 1992). Laboratory experiments confirm the validity of this process (Irving & Major 1964;McIntosh 1993).…”
Section: Discussionmentioning
confidence: 76%
“…Some paleomagnetic studies have suggested that hematite‐bearing, red sedimentary rocks carry a detrital remanent magnetization (DRM) [ Tauxe et al , 1980; Elston and Purucker , 1979; Steiner , 1983; Maillol and Evans , 1992; Garces et al , 1996; Kruiver et al , 2000]. In this case, red bed remanence may acquire a magnetization significantly shallower than the geomagnetic field present during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Burial mechanical compaction can only affect red bed remanence if it is a DRM or a CRM that was acquired early in the post‐depositional history of the sediment. Some workers have suggested that red bed remanence is acquired chemically over long periods of time (Walker et al 1981; Larson et al 1982); others have suggested that haematite‐bearing sedimentary rocks carry a DRM (Elston & Purucker 1979; Tauxe et al 1980; Steiner 1983; Maillol & Evans 1992; Garces et al 1996). While a CRM red bed remanence could be acquired long after deposition, some palaeomagnetic studies of red beds suggest that a chemical remanence was acquired before burial by only 1 m of overburden (Liebes & Shive 1982).…”
Section: Introductionmentioning
confidence: 99%